REKONSTRUKSI PENDEKATAN COMPLIANCE RISK MANAGEMENT DI MASA PANDEMI DALAM UPAYA PENGUATAN PENERIMAAN PAJAK - Prianto Budi Saptono; Khozen, Ismail (Direktorat Jenderal Pajak, 2021)
The Covid-19 pandemic has resulted in a problematic impact on the revenue budget of many countries, including Indonesia. However, when most tax revenues had decreased, personal income tax (PIT) in Indonesia increased. Based on this fact and using a qualitative approach, our study aims to document and analyze a Compliance Risk Management (CRM) approach used to monitor taxpayer compliance in Indonesia. This study analyzes the CRM policy using policy science methods modified according to the CRM implementation and administration scope. Our analysis was carried out primarily by linking the CRM implementation policy with the Covid-19 situation. This study concludes that tax authorities should consider implementing policy strategies under international best practices by adjusting to the current pandemic situation in Indonesia without sticking to each phase. Based on the available alternatives, the Indonesian tax authority needs to consider reconstructing its interaction with taxpayers. The orientation is to provide a stimulus for taxpayers and stay to control their level of compliance.